Comparative study of the physicochemical and palynological characteristics of honey from Melipona subnitida and Apis mellifera - Almeida-Muradian, Ligia Bicudo (2014)
Twenty-four samples of Apis mellifera honey and twenty-four samples of Melipona subnitida (Jandaira) honey were collected in the northeast of Brazil. Moisture, hydroxymethylfurfural, free acidity, insoluble solids in water, diastase activity, ashes, electrical conductivity, proteins, lipids, total carbohydrates, energy and sugars were the parameters analysed. The efficiency of the qualitative tests (Fiehe’s test, Lugol’s reaction, Lund’s reaction) was tested. Pollen types and the corresponding plant species were identified in all samples (3 in Apis and 1 in Melipona). Apis mellifera honey samples demonstrated parameters in accordance with the Brazilian Legislation, while the Melipona subnitida honey samples displayed moisture (24.80%) and diastase activity (null) in discordance with the established by the regulation for Apis mellifera honeys. Apis honey samples presented higher values of electric conductivity (284.00 lS cm 1) than the obtained from the Jandaira honey samples (102.77 lS cm 1) as well as a darker colour (26.67 mmPfund) when compared with Jandaira honey (7.00 mmPfund). The concentration of the glucose, fructose and sucrose was higher in the Apis honeys than in the Jandaira honey. The characteristics of the two types of honey were very different, highlighting the need of developing specific legislation for stingless bees’ honey.